EKSISTENSI UANG DALAM SISTEM EKONOMI ISLAM DAN SISTEM EKONOMI KONVENSIONAL - Amalia Nuril Hidayati (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2018)
AbstractMoney is one of the most important economic instruments. Almost all economic activities are highly dependent on money. Money is a modern innovation that replaces barter positions, or exchanges one item with another. Every economic system has a different view of money. In a conventional economic system, money serves not only as a medium of exchange, a unit of account, nor as a store of value but also serves as a means of payment, as a means of accumulating wealth, and a means of enhancing social status. While the function of money in Islamic economic system there are only two, namely as a medium of exchange and as a unit of account. In the Islamic economic system is also not familiar with money demand for speculation. Because essentially money belongs to God mandated to the temporary owner to be used for the benefit not to serve as a commodity that can be traded. Key words: Money, Islamic Economic System, Conventional Economic System